2020
DOI: 10.1152/ajpendo.00266.2019
|View full text |Cite
|
Sign up to set email alerts
|

Differential intestinal and oral microbiota features associated with gestational diabetes and maternal inflammation

Abstract: Maternal microbiota is involved in many metabolic diseases. However, its role in the pathophysiology of gestational diabetes mellitus (GDM) remains unclear. In this case-control study, we performed a 16S rRNA sequencing-based microbial survey to compare the intestinal and oral microflora at third trimester during pregnancy between 30 GDM and 31 normal controls. Sequentially, a correlation-based network analysis was further performed to explore the interactions among microbiota, maternal and infant blood sugar,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 31 publications
4
72
1
Order By: Relevance
“…This indicates that the dominant microbiota become stable within 16 days. A previous study suggested that Erysipelotrichia and Gammaproteobacteria are closely related to an inflammatory response [43,44], while Mollicutes have been reported to have potential pathogenicity [34]. As previously discussed, the change in Proteobacteria and Actinobacteria may be related to gut microbiota self-regulation.…”
Section: Discussionmentioning
confidence: 80%
“…This indicates that the dominant microbiota become stable within 16 days. A previous study suggested that Erysipelotrichia and Gammaproteobacteria are closely related to an inflammatory response [43,44], while Mollicutes have been reported to have potential pathogenicity [34]. As previously discussed, the change in Proteobacteria and Actinobacteria may be related to gut microbiota self-regulation.…”
Section: Discussionmentioning
confidence: 80%
“…In the following months, the variability of microorganisms decreases, and there is an increase in the populations of Proteobacteria and Actinobacteria ; Bifidobacteria belong to the latter and play a pivotal role in the defense against pathogenic bacteria, in strengthening the intestinal barrier, and in the nutrients' metabolism. The intestine of a pregnant woman can become more permeable favoring the so-called “bacterial translocation” so that the fetus can come into contact with microorganisms of maternal origin (microbes have been found in the blood of the umbilical cord, in the amniotic fluid, and even in the meconium) ( 102 104 ). Furthermore, according to the most widespread theories, the baby's intestine is colonized during childbirth by the bacteria of the maternal microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…This imbalance can also lead to a greater absorption of calories with a consequent weight increase of the pregnant woman and a greater risk of developing GDM. Even the newborn could more easily develop childhood diabetes, allergies, and childhood obesity ( 102 104 ).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the significant changes from late pregnancy to postpartum, no significant variations were found between GDM patients and healthy controls, whether in their third trimester or postpartum, when measured by alpha and beta diversity indexes [24]. However, in another study by Yajuan Xu et al, a significant decrease in salivary microbiota in alpha diversity was found in GDM patients when compared with healthy controls [23]. Given the limitation of the small number of GDM patients in our study, the association between GDM and oral microbiota needs to be further explored.…”
Section: Discussionmentioning
confidence: 82%
“…Obesity is related to the diversity and structure of the salivary microbiome [22]. The oral microbiota could coordinate with glucose metabolism during pregnancy, considering the varying degrees of associations between gestational diabetes mellitus (GDM) and the saliva microbiota [23][24][25].…”
Section: Digiulio Et Al Throughout Pregnancy Based On the 16s Rrna Amentioning
confidence: 99%